Incentives for participation in forest management in the high forest zone of Ghana : gender age and social origin - Boafo, Mercy Serwah (My University, 2000)
The social and economic incentives for community to participate in forest management activities to achieve sustainable management of forests have received very little attention in West Africa. In particular, differences in relation to gender, age and social origin have not been examined. Local communities use the forest for different purposes and have participated in different ways towards the sustainable management of the forest depending on their livelihood and social differences such as gender, age and social origin. Ninety people from four communities comprising two migrant communities, an admitted settlement in the forest reserve and a forest landowning community served as participants for this study. The study utilized participant observation, participant interviews and strategic planning workshops. Local communities value and use forests and forest resources for household subsistence and as a supplementary source of cash income depending on gender, age, social origin and household responsibilities of each individual. Local communities have participated in the management of the forest through forest boundary cleaning, forest rehabilitation, monitoring for illegal activities, prevention of fire outbreaks and forest management planning. Participation in each activity depends on the gender, age and social origin and to some extent the access to collect and gather forest resources. Many people in the local communities were interested in participating effectively and efficiently in the management of the forest if sustainable and secured social and economic incentives are in place. Local communities are interested in participating in forest boundary cleaning, monitoring and reporting illegal activities, controlling and protecting of forest fires, rehabilitating degraded areas of the forest, including thinning and harvesting operations, and in forest management planning. Appropriate incentives for participating effectively and efficiently are dependent on the gender, age and social origin of each individual. These include social and economic incentives such as payment of wages for each activity, access to the forest for gathering and collecting forest resources for both household subsistence and income generation, community development projects, increase in revenue rates, regular payment of revenues, employment for the Juniors and a share in the final crop planted in the forest through rehabilitation work.
Keywords: Forests and forestry Ghana Citizen participation; Social & economic incentives; Sustainable forestry; Non-timber forest products